CtWRKY41 Transcription Factor from Cynanchum thesioides Mediates Salt Stress Resistance and Controls Flowering Time - Xiaoyao Chang; Xiaoyan Zhang; Xiumei Huang; Fenglan Zhang; Zhongren Yang (Plants)
Cynanchum thesioides (Freyn) K. Schum is an ecologically significant species inhabiting the desert and semi-desert regions of northwestern China, distinguished by its remarkable resilience to environmental stressors. Elucidating the functional roles of its stress-responsive genes not only advances the theoretical framework of plant stress tolerance but also provides valuable genetic resources for stress-resilient crop breeding. This study identified a WRKY transcription factor, CtWRKY41, which is strongly induced by salt stress and plays a pivotal role in regulating both flowering time and abiotic stress responses. Subcellular localization analysis confirmed that CtWRKY41 resides in the nucleus and exhibits transcriptional activation activity. Arabidopsis plants overexpressing CtWRKY41 exhibited a significant delay in flowering and enhanced tolerance to salt stress. Further investigation revealed that CtWRKY41 enhances stress resilience by markedly increasing antioxidant enzyme activity, promoting proline accumulation, and upregulating multiple stress-responsive genes. These coordinated mechanisms collectively contribute to the improved salt stress tolerance observed in transgenic Arabidopsis. This study underscores the regulatory significance of CtWRKY41 in plant stress adaptation and establishes a theoretical basis for its potential application in crop genetic improvement programs aimed at enhancing stress resistance.